Energy related activities recognition using smartphones - Goh, Pei Xuan (Nanyang Technological University, 2022)
In this project, the recognition of the activation of energy devices or equipment by its user is in focus. The project aims to investigate the activation of laptop, washing machine and vacuum cleaner using their unique audio signatures. Audio features and machine learning algorithms will be discussed in this report. Neural Network Algorithm will be used in this project to derive high-level information on the usage of activation energy devices by the user. Neural Network is widely used for single event recognition and will be modified and extended in this project to recognize mixed activities and events.